(untitled) (Global Journal of Human-Social Science, 2023)
This article presents a review of the major fitness components associated with success in Brazilian Jiu-Jitsu BJJ athletes with a particular focus on the importance of power training isometric and endurance strength training The review examines the current literature on BJJ and highlights the significance of these fitness components for BJJ athletes to perform at a competitive level The article summarizes the findings from previous research which suggest that power training isometric and endurance strength may be key factors contributing to sporting success in this field 1 This article aims to explore the optimal methods for improving power training isometric and endurance strength in Brazilian Jiu-Jitsu BJJ athletes Through a thorough review of the literature this article discusses the most effective training techniques and programs for enhancing these key fitness components